2016
DOI: 10.1186/s12971-016-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of tobacco smoke induce the production of interleukin-8 in human bronchial epithelium, 16HBE cells

Abstract: BackgroundInterleukin-8 (IL-8) functions as a major chemoattractant and plays pivotal roles in the initiation and development of chronic obstructive pulmonary disease (COPD), and tobacco smoke is a most risk factor contributing to the development of COPD. Hence, we have screened some of the tobacco smoke-derived chemical compounds that potentially induce the production of IL-8 in human bronchial epithelium, 16HBE cells.MethodsTwenty-eight hazardous smoke components belonging to 9 classes including nicotine, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…Interestingly, this response was totally reverted by treatment with NAC, suggesting that a ROS signaling, induced by CSE, is involved in the production of these proinflammatory cytokines. This is in agreement with prior publications in other model systems [19] , [48] , [49] , [50] , [51] . It is important to highlight that the increased cytokine levels were induced directly by CSE, in absence of bacterial infection (aseptic or sterile inflammation) or LPS stimulation, as it has been proposed by other authors [19] , [48] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, this response was totally reverted by treatment with NAC, suggesting that a ROS signaling, induced by CSE, is involved in the production of these proinflammatory cytokines. This is in agreement with prior publications in other model systems [19] , [48] , [49] , [50] , [51] . It is important to highlight that the increased cytokine levels were induced directly by CSE, in absence of bacterial infection (aseptic or sterile inflammation) or LPS stimulation, as it has been proposed by other authors [19] , [48] .…”
Section: Discussionsupporting
confidence: 94%
“…It is important to highlight that the increased cytokine levels were induced directly by CSE, in absence of bacterial infection (aseptic or sterile inflammation) or LPS stimulation, as it has been proposed by other authors [19] , [48] . Zhou et al [51] identified different CSE compounds that could induce the production of IL-8 in human epithelium bronchial 16HBE cells, suggesting that the chemical composition of the CSE could start the inflammatory phenotype in COPD, previously to any bacterial infection. Also, Ko et al observed that CSE exposure induces IL-8 release from macrophages mediated by ROS activation of NF-κB through the AMP-activated protein kinase (AMPK).…”
Section: Discussionmentioning
confidence: 99%
“…~2-20 μg/mL) are in the range used in other in vitro studies with human bronchial cells, where toxic PAH effects were reported for concentrations between 1-500 μg/mL or 1-200 μM (Abbas et al, 2019;Cervena et al, 2017;Chang et al, 2019). In agreement with previous studies (Blaha et al, 2002;Kubincová et al, 2019;Zhou et al, 2016), no major cytotoxic responses were detected up to 100 μM concentrations of the tested PAHs in HBE1, which indicates that GJIC inhibition was probably not caused by general cellular response to membrane damage or cytotoxic stress. Since membrane and intracellular accumulation of PAHs by Cx43-expressing TM3 and TM4 cells did not correlate with the inhibition of GJIC (Kubincová et al, 2019), the effects of PAHs on GJIC do not seem to be caused by their direct interaction with Cx proteins.…”
Section: Discussionsupporting
confidence: 88%
“…Gudzinowicz identified more chemical substances in tobacco leaf in 1980 [ 26 ]. The US Food and Drug Administration (FDA) and “Hoffman analytes” lists both have identified “harmful and potentially harmful” constituents in tobacco products, including two classes of compounds that have garnered significant attention: polycyclic aromatic hydrocarbons, mainly benzo[ a ]pyrene, and Nitrosamines (N-nitrosodiethylamine (NDEA), N-nitrosodiethanolamine (NDELA), N-nitrosodimethylamine (NDMA), N-nitrosomethylethylamine (NMEA), N-nitrosomorpholine (NMOR), 4-(methylnitrosamino)- 1-(3-pyridyl)-1-butanone (NNK), N-nitrosonornicotine (NNN), N-nitrosopiperidine (NPIP), N-nitrosopyrrolidine (NPYR), and N-nitrososarcosine (NSAR)), especially NNK [ 27 , 28 ]. (Fig.…”
Section: Tobacco Nitrosoaminesmentioning
confidence: 99%